Pengaruh Sumber Daya Manusia, Gaya Kepemimpinan dan Etos Kerja terhadap Kinerja Kerja Pegawai Dinas Koperasi dan UKM Provinsi Kepulauan Riau - Firman, Firman; Sholeh, Chaereyranba (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2021)
The aims of this research are to find out and analyze the influence of human resources, leadership style and work ethic of employees performance in Cooperatives and SME office in Kepulauan Riau Province. This research is an explanatory research which explains the relationship between the variables through testing hypotheses. The sampling technique uses representative sampling method. Sampling of the research amounted to 69 employees, samples taken from the entire population. The instrument for measuring the variation of questions is using the Likert Scale with a score of 1-5. Data analysis techniques using SPSS (Statistical package for social sciences). The results of the research shows that partially human resources and leadership style have a significant effect on work performance except work ethic has no significant effect and all dependent variables simultaneously influence towards work performance. Based on the results of this research, some recommended for practical implementation are organizational work ethic will be associated with higher work performance and strengthen the effectiveness of leadership style through the determination of leader.